2022
DOI: 10.3389/fneur.2021.711470
|View full text |Cite
|
Sign up to set email alerts
|

Transitional and Long-Term Care System in Japan and Current Challenges for Stroke Patient Rehabilitation

Abstract: In Japan, the national medical insurance system and long-term care insurance (LTCI) system cover rehabilitation therapy for patients with acute, convalescent, and chronic stroke. Medical insurance covers early and multidisciplinary rehabilitation therapy during acute phase hospitalizations. Patients requiring assistance in their activities of daily living (ADL) after hospitalization are transferred to kaifukuki (convalescent) rehabilitation wards (KRW), which the medical insurance system has also covered. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Unlike Western countries, such as the USA and Europe, most cities in China have primary, secondary, and tertiary hospitals corresponding to the acute, convalescent, and chronic phases of stroke. Some Asian countries refer to the second level of three-level rehabilitation as transitional rehabilitation ( Leigh et al, 2022 ), which does not change the fact that they also practice three-level rehabilitation ( Kinoshita et al, 2021 ). In China, many studies have confirmed that the three-level stroke rehabilitation network is beneficial for rehabilitation of stroke patients, and was recommended by the Chinese Stroke Association guidelines for clinical management of cerebrovascular disorders ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Western countries, such as the USA and Europe, most cities in China have primary, secondary, and tertiary hospitals corresponding to the acute, convalescent, and chronic phases of stroke. Some Asian countries refer to the second level of three-level rehabilitation as transitional rehabilitation ( Leigh et al, 2022 ), which does not change the fact that they also practice three-level rehabilitation ( Kinoshita et al, 2021 ). In China, many studies have confirmed that the three-level stroke rehabilitation network is beneficial for rehabilitation of stroke patients, and was recommended by the Chinese Stroke Association guidelines for clinical management of cerebrovascular disorders ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The officials advocate the establishment of a three-level stroke rehabilitation service system ( Chen et al, 2010 ), with primary rehabilitation for acute and sub-acute stroke rehabilitation in tertiary hospitals or tertiary rehabilitation hospitals, secondary rehabilitation for convalescent phase of stroke in secondary hospitals or secondary rehabilitation hospitals, and tertiary rehabilitation for chronic phase of stroke in community health service centers or township health centers or families. Although the three-level stroke rehabilitation system has established recommended referral criteria and treatment protocols ( Xu et al, 2021 ), the lack of uniform management practices across all levels of care may delay the treatment due to poor referral, indicating that coordinating the treatment of stroke patients between the acute, convalescent, and chronic phases is essential ( Kinoshita et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…During rehabilitation by LTCI, doctors’ instructions are required before starting rehabilitation through LTCI. In Japan, LTCI helps in the seamless transition between treatments from acute to chronic phases to improve and maintain functional activity of patients 6 . Disease-specific rehabilitation in each clinical department is widely recognized 7 and has been established in Japan 8 – 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in the length of hospital stay (LOS) among patients is one aspect of this strategy. In Japan, which has a super-aged society, the shift from hospital care to community care, including shortening of the LOS, has been promoted as a health policy based on the Community-based Integrated Care System [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%